2007
DOI: 10.1128/jvi.02353-06
|View full text |Cite
|
Sign up to set email alerts
|

TopBP1 Regulates Human Papillomavirus Type 16 E2 Interaction with Chromatin

Abstract: Human papillomavirus type 16 (HPV16) E2 regulates transcription from and replication of the viral genome, in association with viral and cellular factors. HPV16 E2 interacts functionally with TopBP1, a cellular protein essential for the initiation of cellular, and potentially viral, DNA replication. This report demonstrates that the absence of TopBP1 results in the redistribution of HPV16 E2 into an alternative cellular protein complex, resulting in enhanced affinity for chromatin. This redistribution does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 23 publications
3
69
2
Order By: Relevance
“…We show that E2 induces a marked relocalization of the E7 protein from the soluble fraction to the insoluble fraction of the cell. Because previous studies had shown that E2 is largely associated with chromatin (Kurg et al, 2005;Donaldson et al, 2007), it is tempting to suggest that E2 is also recruiting E7 onto chromatin-containing complexes. At present it is not clear what this recruitment might mean for E7 function, although it is conceivable that this may result not only in the regulation of some E7 functions as reported here, but also in the gain of other, as yet unknown, activities of the protein.…”
Section: Rt-pcrmentioning
confidence: 99%
“…We show that E2 induces a marked relocalization of the E7 protein from the soluble fraction to the insoluble fraction of the cell. Because previous studies had shown that E2 is largely associated with chromatin (Kurg et al, 2005;Donaldson et al, 2007), it is tempting to suggest that E2 is also recruiting E7 onto chromatin-containing complexes. At present it is not clear what this recruitment might mean for E7 function, although it is conceivable that this may result not only in the regulation of some E7 functions as reported here, but also in the gain of other, as yet unknown, activities of the protein.…”
Section: Rt-pcrmentioning
confidence: 99%
“…Binding of E2 to Brd4, ChlR1, and Mklp2 has been implicated in mediating the plasmid segregation function of E2 (4,36,47,82). Transcriptional activation by E2 depends upon binding to several cellular proteins, such as Brd4, cNAP1, Gps2, p300, and TopBP1 (7,16,27,39,49). E2 has also been shown to repress the HPV E6/E7 promoter from promoter-proximal binding sites (70).…”
Section: This Suggests That Repression Of the E6/e7 Promoter By E2 Anmentioning
confidence: 99%
“…A candidate protein for mediating host chromatin attachment for some E2 proteins is Brd4 (13). Colocalization of HPV16 E2 with the cellular partner protein TopBP1 at mitosis suggests that this protein may also play a role in segregation of the HPV16 genome (14). However, Brd4 is required for the optimal transcriptional activation and repression properties of all E2 proteins tested to date (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
mentioning
confidence: 99%